CSF1R Ligands IL-34 and CSF1 Are Differentially Required for Microglia Development and Maintenance in White and Gray Matter Brain Regions - Easley-Neal, Courtney; Foreman, Oded; Sharma, Neeraj; Zarrin, Ali A.; Weimer, Robby M (Frontiers in Immunology, 2019)
Microglia are specialized brain macrophages that play numerous roles in tissue homeostasis and response to injury. Colony stimulating factor 1 receptor (CSF1R) is a receptor tyrosine kinase required for the development, maintenance, and proliferation of microglia. Here we show that in adult mice peripheral dosing of function-blocking antibodies to the two known ligands of CSF1R, CSF1 and IL-34, can deplete microglia differentially in white and gray matter regions of the brain, respectively. The regional patterns of depletion correspond to the differential expression of CSF1 and IL-34. In addition, we show that while CSF1 is required to establish microglia in the developing embryo, both CSF1 and IL-34 are required beginning in early postnatal development. These results not only clarify the roles of CSF1 and IL-34 in microglia maintenance, but also suggest that signaling through these two ligands might support distinct sub-populations of microglia, an insight that may impact drug development for neurodegenerative and other diseases.